The first lumpy skin disease outbreak in cattle in Kazakhstan - Issimov, A.M.; Kemalova, N.K.; Sarzhigitova, A.T.; Bakytzhankyzy, B. (Fundamental and Experimental Biology, 2023)
Lumpy skin disease (LSD) is an emerging trans-boundary viral disease of cattle originating from the African continent. Here, we describe the first LSD outbreak reported in the Republic of Kazakhstan in July 2016, as well as associated clinical manifestations of the disease, diagnostic methods, and control measures taken to combat further spread of the pathogen. To determine the cause of the disease, samples were taken from sick and dead animals, as well as from insects and ticks. LSDV DNA was detected by PCR in all samples from dead animals and ticks (Dermacentor marginatus and Hyalomma asiaticum), in 14.29% of samples from horseflies (Tabanus bromius), and in one of the samples from two Stomoxys calcitrans flies. The reproductive LSD virus was isolated from organs of dead cattle and insects in the culture of LT and MDBK cells. The virus accumulated in cell cultures of LT and MDBK at the level of the third passage with titers in the range of 5.5–5.75 log 10 TCID50/cm3.During the outbreak, the number of affected cattle within an epidemiological unit reached 459 cattle out of 3557 registered susceptible cattle, with 12.90% morbidity and 0.96% mortality. This manuscript presents the epidemiological situation; the diagnosis; the control measures, including mass vaccination; and the stamping out campaign.